Early Detection of Caries and Efforts to Prevent Dental Caries in Retardation Mental Children Through Empowering Teachers and Parents at SLB BC Optimal Surabaya - Ulfah, Siti Fitria; Agus Marjianto (Frontiers in Community Service and Empowerment, 2023)
Dental caries is a disease of the hard tissue of the teeth which is characterized by tissue damage, starting from the tooth surface, starting from the enamel, dentin, and extending to the pulp. Dental caries in mentally retarded people is in the moderate category. The data update for SLB BC Optimal Surabaya in 2021 revealed that 100% of the mentally disabled experienced dental caries. Dental caries in mentally retarded children can be prevented by their parents and teachers. Their involvement is very important to achieve optimal dental health in mentally retarded children. The method used is: Starting from permits to partners, target preparation, community service team, materials, tools and materials needed. Providing physical assistance to parents and teachers in the form of tools/materials to support oral physiotherapy and tools/materials to detect dental caries. Training/Counseling on the consequences of dental caries if no treatment is carried out and how to prevent dental caries, definition of dental caries, causes of dental caries, process of dental caries, how to detect early dental caries. The results of the community service activities that have been carried out have obtained the following results: Module for early detection of dental caries and prevention of dental caries. There is an increase in knowledge of dental caries and prevention of dental caries for teachers and parents at SLB BC Optimal Surabaya from 51.2% to 80%. There is an increase The attitude of parents and teachers about dental caries was 65.7% negative. After training, the positive attitude of parents and teachers regarding dental caries was 71.4%. There was an increase in respondents' skills in early detection of caries from 25% to 80%. There was an increase in parents' and teachers' skills regarding preventing dental caries from 15% to 63%.